You've got plaid - Knight, Eliza (Knight, Eliza. Prince Charlie's angels, 2021)
"Brogan Grant, a Jacobite soldier and bastard son of the Chief, fought savagely on the battlefield and barely escaped capture. On the run for his life, Brogan comes across what he thinks is a spy--a very bonny lass disguised as a lad, who happens to be the daughter of his clan's enemy. He admires her bravery, but he knows what can happen to a woman alone in a war-ravaged land. Lady Fiona MacBean is determined to do her part to ensure there is a Scottish king. Disguised as a healer, she delivers coded messages to rebels throughout the Highlands. There's only one thing impeding her mission--a striking Highlander who's determined to send her home."--Provided by publisher.